Análise cristalográfica de cálculos urinários e sua associação com fatores metabólicos, climáticos e índice de desenvolvimento humano na população brasileira - Cunha, Tamara Da Silva [UNIFESP] (2020)
The frequency of renal stones in Brazil has been evaluated in the last 30 years by investigators from the areas of Urology and Nephrology based on epidemiological data focused on the number of admissions in the emergency room and hospitalization due to episodes of renal colic. However, there is scarce data in Brazil evaluating kidney stone composition using physical analysis as proposed by international guidelines. Moreover, variations in demographic, economic and environmental factors might influence the worldwide distribution of urolithiasis but scarce data is available concerning their associations with stone composition worldwide. The aims of the present study were to evaluate the frequency and composition of kidney stones and their associations with temperature, humidity and human development index (HDI) in different parts of a large country as Brazil, presenting with a handful of social contrasts and a wide variation of climate. A total of 1,158 stones from distinct regions of the country were submitted to physical analysis, and the mean annual temperature and relative humidity of each city were considered separately. A sub-group of patients (n=204) whose 24hr urine samples were available, were tested for associations with metabolic disturbances. Calcium oxalate (CaOx) stones were disclosed in 60.9% (monohydrate and dihydrate) of patients followed by uric acid stones (pure/mixed with CaOx monohydrate) in 16.7%, pure or mixed apatite/CaOx dihydrate in 11.3%, struvite in 8.3%, brushite in 1.8% and cystine/rare types in 0.8%. People living in cities with a HDI < 0.800 had twice the odds of having a struvite stone versus those living in a HDI ≥ 0.800 (OR=2.14, 95% CI 1.11–4.11). A progressive increase in the frequency of struvite stones from 4.5% to 22.8% was detected between a HDI higher than 0.800 through lower than 0.700. No significant differences for other stone types were disclosed. In separate logistic regression models assessing the association of each stone composition with covariates, no significant association was detected with climate. Among patients whom underwent 24-hour urinary metabolic workup, no significant differences were observed in comparison to the literature. In conclusion, patients living in areas with low HDI were more prone to developing struvite stones, possibly due to a more restricted access to healthcare. Temperature and humidity did not represent an independent risk factor for any stone type in our population.